E-records management in Tanzania public service: determinants, perceived importance and barriers - Newa, Judith Romwald; Mwantimwa, Kelefa (University of Dar es Salaam Library Journal, 2020)
Despite rigorous efforts by the government to introduce an e-government, most of the records in the public service of Tanzania are not electronically managed. The present study was conducted to assess records staff ' s awareness of e-records management determinants, explore the perceived importance of e-records management, and analyse challenges of managing e-records in the Records and Archive Management Department (RAMD) of Tanzania. A descriptive research design alongside qualitative and quantitative approaches was utilized to collect, process, and analyse data in this study in which a 38 respondents were involved. Data for this study were collected using a cross-sectional survey (i.e. questionnaire and interview) and documentary review. The study ' s findings reveal that determinant factors for e-records management are not in a state to speed up the take-off of e-records management initiatives of the RAMD. Shortage of competent staff for e-records management, dwindling of budget to support training and maintenance of infrastructure, and weak implementation of policies, circulars, and standards are among the challenges faced by efforts to manage e-records. Despite the slow take-off of e-records management initiatives, the responding staff perceived their management positively. Success in e-records management initiatives evidently requires the presence of reliable supporting environment and readiness tools such as standards, infrastructure, circulars, and policies.